การประเมินความเสี่ยงเชิงปริมาณและแบบจำลองความน่าจะเป็นของการปนเปื้อนเชื้อซัลโมเนลลาที่เพาะแยกได้จากกระบวนการผลิตสุกรใน ฟาร์มแม่พันธุ์ เปรียบเทียบระหว่างฟาร์มสุกรในรูปแบบการเลี้ยงแบบสหกรณ์และฟาร์มสุกรในรูปแบบการเลี้ยงแบบครบวงจรในเขตภาคเหนือตอนบนของประเทศไทย - ดนัย สินธุยะ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objectives of this study were to determine the prevalence and number of Salmonella contamination in swine breeding unit production system in upper-northern part of Thailand. Outcomes were compared between two different swine production patterns at farm level which were co-operative farm type and integrated commercial swine farms. The prevalence of Salmonella-contaminated sows were 32.69% and 25.00% (p-value>0.05), and the average Most Probable Number (MPN) of Salmonella contaminated were 2.08 LogMPN/g and 1.75 LogMPN/g in each type of farm, respectively. The prevalence of Salmonella in boars was detected at 25.00% and 37.50% (p-value>0.05) with an average 2.07 LogMPN/g and 2.44 LogMPN/g, respectively. The prevalence of Salmonella in piglets were 33.33% and 12.50% (p-value<0.05) with the MPN average at 2.01 LogMPN/g and 1.80 LogMPN/g, respectively. Feed is a risk factor of Salmonella contamination in breeding-swine farms. Feed from co-ooperative farm can cause Salmonella contamination 3 times from integrated commercial farm feed. (p-value=0.048, OR=3.17, 95%CI:1.01-9.97) This study showed swine breeding units were one of major source of Salmonella contamination in primary stage of swine production and may lead to contamination throughout the food chain. In order to minimize salmonellosis in human resulting from contaminated pork consumption, reduction of Salmonella contamination in swine breeding unit is also inevitably required.